Going for the Blue Ribbon: The Legality of Expert Juries in Patent Litigation - Fisher, Michael (Science and Technology Law Review, 2001)
In “Going for the Blue Ribbon: the Legality of Expert Juries in Patent Litigation”, the author discusses the legality and practicality of employing “blue ribbon” – i.e. expert – juries in certain patent litigation. The use of such juries, it is argued, would reduce the arbitrariness of and restore fairness to the adjudicative process in light of the complex technical and scientific issues frequently encountered in patent litigation. The author demonstrates how these special juries would resolve the tension between two competing constitutional guarantees: the right to a trial by jury, under the Seventh Amendment, and the right to due process (and a minimum level of juror competency implied by such right), under the Fifth Amendment. It is even suggested that there may be a constitutional obligation to provide a sufficiently skilled jury in patent cases. The note then addresses potential legal barriers to blue ribbon juries – particularly the “fair cross section requirement” for juries under the Equal Protection Clause – and presents case-law and demographic evidence demonstrating how these barriers could be overcome. Finally, the author examines the practical considerations of employing blue ribbon juries, concluding that the federal court system could accommodate such a measure through its existing infrastructure, and that sufficient jurors could be obtained from society’s pool of “experts”.